2020
DOI: 10.1080/10962247.2020.1726838
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of real-life operating patterns of wood-burning appliances using stack temperature data

Abstract: A study was undertaken to identify patterns of consumer use of outdoor wood boilers or outdoor wood furnaces (technically referred to as outdoor wood-fired hydronic heaters (OWHHs)) and indoor wood stoves (IWSs) to inform the development of performance testing protocols that reflect real-life operating conditions. These devices are manually fed, and their usage protocols are a function of a number of variables, including user habits, household characteristics, and environmental factors. In this study, research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Similarly, procedures for EPA ALT-140 are based on temperature data collected from 20 US homes over one or two heating seasons. This study indicated that temperature profiles of the external wall of the stack were highly irregular, and they were not able to accurately capture fuel reloading events [45]. Given the diversity of user behavior, laboratory test cycles must balance between accurately representing residential operation and providing replicable experimental procedures for consistently characterizing heater performance.…”
Section: Test Cyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, procedures for EPA ALT-140 are based on temperature data collected from 20 US homes over one or two heating seasons. This study indicated that temperature profiles of the external wall of the stack were highly irregular, and they were not able to accurately capture fuel reloading events [45]. Given the diversity of user behavior, laboratory test cycles must balance between accurately representing residential operation and providing replicable experimental procedures for consistently characterizing heater performance.…”
Section: Test Cyclesmentioning
confidence: 99%
“…The fundamental purpose of the test cycle is to provide uniform operating conditions for repeatably evaluating and comparing heater performance. While this is useful for establishing compliance to regulations, the emissions and performance results may not be representative of residential operation [11][12][13][14][15]45,46]. For example, many test methods do not account for start-up, cool-down, fuel loading, and other transient periods that occur during normal operation.…”
Section: Test Cyclesmentioning
confidence: 99%
See 1 more Smart Citation